PENGGUNAAN RUANG GURU PADA PEMBELAJARAN TEKS ULASAN DI SMP NEGERI 2 SERIRIT - Kadek Putri Indah Lestari Indah; I Nyoman Yasa; Ade Asih Susiari Tantri (Dharmas Education Journal (DE_Journal), 2021)
This study aims to describe the implementation of learning to write review texts using the Teacher's Room at SMP Negeri 2 Seririt. The subjects of this study were Indonesian language teachers and eighth grade students of SMP Negeri 2 Seririt. The object of this research is the implementation of learning to write review texts using the Teacher's Room, and the obstacles faced in learning. Data collection uses observation methods, interview methods, and documentation methods. The research instruments include observation sheets and unstructured interviews. Data analysis was carried out according to the qualitative descriptive analysis model with four stages, data reduction, data classification, data description, and conclusions. The results of this study include (1) the implementation of review text learning with Ruang Guru at SMP Negeri 2 Seririt through 3 activity stages namely, preliminary activities, core activities, and closing activities. The facilities and infrastructure used in the implementation of learning include: laptops, teaching videos in the Teacher's Room, and gadgets. (2) The obstacles faced in learning review texts with Ruang Guru at SMP Negeri 2 Seririt focused on online learning which included: some students were late joining the WhatsApp Group class (b) some students did not have learning support facilities, (c) network uneven, (d) the initial motivation of students is not optimal, and (e) some parents have not been able to support learning facilities and infrastructure